2003
DOI: 10.1002/mpo.10295
|View full text |Cite
|
Sign up to set email alerts
|

Marked osteoporosis and spontaneous vertebral fractures in children: Don't forget, it could be leukemia

Abstract: Children with acute lymphoblastic leukemia (ALL), the most common childhood malignancy, usually present at diagnosis with signs of bone marrow failure. Pallor, fatigue, anemia, fever, neutropenia, and thrombocytopenia are frequent signs. Skeletal manifestations on imaging studies are found in 20-36% of cases [1,2]. These include metaphyseal bands, periosteal new bone formations, lytic lesions, osteosclerosis, osteopenia, and mixed osteolysis and sclerosis [1][2][3]. Generalized osteopenia and vertebral complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Some studies have reported that up to 30% of children have decreased BMD at diagnosis and 15-29% of ALL survivors have diminished BMD [17,18]. Skeletal changes are found in 20-36% of ALL cases [19] and up to 39% of children end up with fractures by completion of therapy [16].…”
Section: Increased Risk For Osteoporosis In Children With Cancermentioning
confidence: 97%
“…Some studies have reported that up to 30% of children have decreased BMD at diagnosis and 15-29% of ALL survivors have diminished BMD [17,18]. Skeletal changes are found in 20-36% of ALL cases [19] and up to 39% of children end up with fractures by completion of therapy [16].…”
Section: Increased Risk For Osteoporosis In Children With Cancermentioning
confidence: 97%
“…111 Moreover, following the administration of gadolinium, bone marrow in young children can enhance heterogeneously and should not be confused with tumor infiltration. 47 Pathologic vertebral compression fractures can be a manifestation of acute lymphoblastic leukemia in childhood, 112,113 secondary to severe osteoporosis and occurring in 1%-7% of patients diagnosed with this cancer.…”
Section: Lymphoma and Leukemiamentioning
confidence: 99%
“…Rare cases of ALL presenting with severe osteoporosis and spontaneous humerus fractures have also been described [5][6][7][8][9]. It has been suggested that pathological fractures are present at the time of diagnosis in approximately 1% of cases of acute lymphoblastic leukemia (ALL) [10].…”
mentioning
confidence: 99%